Decolonizing Indian History (Global Journal of Human-Social Science, 2014)
The process of the decolonizing Indian history, though seems to start with the independence of India in 1947, it actually originates in the high noon of colonialism in India in the middle of the nineteenth century. So, the present discussion begins with a prelude which contains the history of increasingly growth of conciousness among Indians which culminated in the development of nationalism among the largest section of the people. But in developing national view the interests of the minority, particularly Muslims, who form one of the most important constituents of the national economy of India, were not duly attended. Such situation led to the achievement of independence with a partition. After partition, the transformation from colonialism to decolonization began with a quest for establishing an idea of India. A constitution was adopted which insists on multitudinous democracy, unity in diversity, secularity with unlimited liberty of professing religion and social democracy with leniency towards capitalism.
Keywords: communitarian two nation theory; bureaucracy; populism; majoritarian; blood bath